Efektivitas Pelaksanaan Undang-Undang No 32 Tahun 2009 Tentang Perlindungan Dan Pengelolan Lingkungan Hidup Terhadap Tambang Emas Ilegal - Dermina Dalimunthe, Linda Sari & (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
The amount of pollution produced by the community is increasing as a result of technological advancements. The government passed Law No. 32 of 2009 on Environmental Conservation and Management. The regulations govern the disposal of B3 waste, which contains substances, energy, or other components that, directly or indirectly, pollute the environment and endanger human health. The survival of living things as a result of illegal gold mining in Hutabargot Nauli Village. There are still many violators, despite the fact that enforcement has not been effective. This is evidenced by the increasing number of offenders each year. The research question is,